2021
DOI: 10.1038/s41598-021-88025-w
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver index is independently associated with deterioration of renal function during a 10-year period in healthy subjects

Abstract: A potential link between chronic kidney disease (CKD) and non-alcoholic fatty liver disease (NAFLD) has been suggested. We investigated the relationship between fatty liver index (FLI), a noninvasive and simple predictor of NAFLD, and the development of CKD defined as estimated glomerular filtration rate < 60 mL/min/1.73 m2 or positive for urinary protein during a 10-year follow-up period in subjects who received annual health examinations (n = 28,890). After exclusion of CKD at baseline, a total of 14,163 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Evidence illustrates that the GFR deterioration was associated with progressive impairment in uric acid excretion. 39 , 40 To eliminate the influence of GFR on UUAE, we further analyzed the association between UUAE and obesity and abdominal obesity in the CKD group and non-CKD group. Finally, we found that UUAE was significantly related to obesity and abdominal obesity only in the non-CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence illustrates that the GFR deterioration was associated with progressive impairment in uric acid excretion. 39 , 40 To eliminate the influence of GFR on UUAE, we further analyzed the association between UUAE and obesity and abdominal obesity in the CKD group and non-CKD group. Finally, we found that UUAE was significantly related to obesity and abdominal obesity only in the non-CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…This dose-response metaanalysis supports a direct association between FLI and HR of incident T2D address this topic, and both seem to confirm the notion that FLI predicts CKD. Sun et al [65] conducted a population-based study on 9436 adult Chinese subjects. The data show that, in logistic regression analysis, compared to those within the lowest FLI quartile, the adjusted ORs of those in the highest FLI quartile were 2.30 (95%CI: 1.36-3.90) for increased urinary albumin excretion and 1.93 (95%CI: 1.18-3.15) for CKD.…”
mentioning
confidence: 99%
“…In the first, noninvasive fibrosis scoring systems significantly predicted CKD [35], while in the study by Am et al, a higher score of portal inflammation was associated to a 7.7-fold increased risk of renal outcomes [37]. Finally, Takahashi et al suggested the addition of FLI, a noninvasive marker of steatosis, into traditional risk factors for CKD because they found a discriminatory capability of high level of FLI for prediction of CKD in both sexes in a general population [39].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD was diagnosed by abdominal ultrasound in five studies [30][31][32][33][34], only three studies used the gold-standard liver biopsy [35][36][37], two studies used the fatty liver index (FLI) [38,39], one study used the fibrosis-4 (FIB-4) score [40] and one study enrolled NAFLD patients by the 10th revision of the International Classification of Diseases (ICD-10) [41]. The diagnosis of CKD was performed according to The Kidney Disease: Improving Global Outcomes 2012 Clinical Practice Guideline as the reduction of GFR < 60 mL/min/1.73 m 2 estimated by different formulae in almost all the studies (KDIGO 2012), except for one study that used the International Classification of Diseases, 10th revision (ICD-10) [41].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation